Optimalisasi penanganan kasus prostetik dengan perawatan ortodontik Optimalization of prosthetic case management with orthodontic treatment - Eddy Heriyanto Habar (DiscoverSys Inc., 2011)
Management of certain prosthetic cases can be established with optimal result when prior orthodontic treatment isundertaken, such as example cases of missing teeth with diastema or abnormal arch form. A 24-year-old femalepatient came with the complaint of diastema as a result of tooth loss and need a denture. After the examination, itwas found that the teeth were unarranged and the arch form was abnormal. Orthodontic treatment was firstlyundertaken to arrange the teeth, establish the space for denture and fix the arch form. The denture was made afterfinishing the orthodontic treatment.